Analysis of the microcirculation after soft tissue reconstruction of the outer ear with burns in patients with severe burn injuries. Issue 7 (July 2016) - Medved, Fabian; Medesan, Raluca; Rothenberger, Jens Martin; Schaller, Hans-Eberhard; Schoeller, Thomas; Manoli, Theodora; Weitgasser, Lennart; Naumann, Aline; Weitgasser, Laurenz
Summary: Reconstruction of soft tissue defects of the ear with burns remains one of the most difficult tasks for the reconstructive surgeon. Although numerous reconstructive options are available, the results are often unpredictable and worse than expected. Besides full and split skin grafting, local random pattern flaps and pedicled flaps are frequently utilized to cover soft tissue defects of the outer auricle. Because of the difficulty and unpredictable nature of outer ear reconstruction after burn injury, a case–control study was conducted to determine the best reconstructive approach. The microcirculatory properties of different types of soft tissue reconstruction of the outer ear with burns in six severely burned Caucasian patients (three men and three women; mean age, 46 years (range, 22–70)) were compared to those in the healthy tissue of the outer ear using the O2C device (Oxygen to See; LEA Medizintechnik, Gießen, Germany). The results of this study revealed that the investigated microcirculation parameters such as the median values of blood flow (control group: 126 AU), relative amount of hemoglobin (control group: 59.5 AU), and tissue oxygen saturation (control group: 73%) are most similar to those of normal ear tissue when pedicled flaps based on the superficial temporal artery were used. These findings suggest that this type of reconstruction is superior for soft tissue reconstruction of the outer ear with burns in contrast to random pattern flaps and full skin grafts regarding the microcirculatory aspects. These findings may improve the knowledge on soft tissue viability and facilitate the exceptional and delicate process of planning the reconstruction of the auricle with burns.